2020
DOI: 10.1002/rth2.12438
|View full text |Cite
|
Sign up to set email alerts
|

MG1113, a specific anti–tissue factor pathway inhibitor antibody, rebalances the coagulation system and promotes hemostasis in hemophilia

Abstract: Background Replacement therapy is the most common treatment for reduction of bleeding and control of episodic bleeding in individuals with hemophilia. Despite the proven effectiveness of factor replacement therapy, repeated intravenous administration is a heavy burden to individuals with hemophilia. Objectives To reduce the burden, therapeutic agents that can be subcutaneously administered need to be developed, and an anti–tissue factor pathway inhibitor (TFPI) antibody may be a suitable candidate for this pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 25 publications
(36 reference statements)
1
8
0
Order By: Relevance
“…The restoration of thrombin generation with this single monoclonal antibody is consistent with a central role for the binding of the second Kunitz domain to the active site of FXa in the TFPIα anticoagulant activity producing bleeding in these patients, which may be mediated by its role in the inhibition of TF‐FVIIa 9 or prothrombinase 19 . In this regard, there are several humanized anti‐TFPI monoclonal antibodies directed against the second Kunitz domain presently in clinical trials for hemophilia as a non‐factor therapy for prophylaxis 25‐29 . It remains to be determined if these may hold promise as a prophylactic agent for severe spontaneous bleeding episodes in some patients with FV‐short 5 …”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…The restoration of thrombin generation with this single monoclonal antibody is consistent with a central role for the binding of the second Kunitz domain to the active site of FXa in the TFPIα anticoagulant activity producing bleeding in these patients, which may be mediated by its role in the inhibition of TF‐FVIIa 9 or prothrombinase 19 . In this regard, there are several humanized anti‐TFPI monoclonal antibodies directed against the second Kunitz domain presently in clinical trials for hemophilia as a non‐factor therapy for prophylaxis 25‐29 . It remains to be determined if these may hold promise as a prophylactic agent for severe spontaneous bleeding episodes in some patients with FV‐short 5 …”
Section: Discussionsupporting
confidence: 57%
“…19 In this regard, there are several humanized anti-TFPI monoclonal antibodies directed against the second Kunitz domain presently in clinical trials for hemophilia as a non-factor therapy for prophylaxis. [25][26][27][28][29] It remains to be determined if these may hold promise as a prophylactic agent for severe spontaneous bleeding episodes in some patients with FV-short. 5 Interestingly, in our pedigree, three affected individuals have reported delayed wound healing with one suffering from recurrent angular cheilitis that did not heal properly and persisted for more than a year.…”
Section: Discussionmentioning
confidence: 99%
“…The in vitro studies demonstrated that MG1113 binds to free TFPI of humans, monkeys, and rabbits. Accordingly the in vivo efficacy (modified prothrombin time, activated partial thromboplastin time, and hemoglobin loss) was observed after the administration of MG1113 to the rabbit hemophilia model 12 . The TFPI inhibitor products (fucoidan and PF‐06741086) and Aptamer ARC19499 have been shown to block FXa inhibition by TFPI, restore hemostasis, and reduce blood loss in hemophilia A mice and hemophilia‐induced monkey models 13–15 .…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly the in vivo efficacy (modified prothrombin time, activated partial thromboplastin time, and hemoglobin loss) was observed after the administration of MG1113 to the rabbit hemophilia model. 12 The TFPI inhibitor products (fucoidan and PF-06741086) and Aptamer ARC19499 have been shown to block FXa inhibition by TFPI, restore hemostasis, and reduce blood loss in hemophilia A mice and hemophilia-induced monkey models. [13][14][15] The in vitro and in vivo potency results of concizumab, an antibody with properties most similar to those of MG1113, have also been reported in hemophilia-induced rabbits.…”
Section: Introductionmentioning
confidence: 99%
“…MG1113 is humanised IgG4 monoclonal antibody that binds to the Kunitz-2 domain (K2) of TFPI. It has been shown in vitro to restore thrombin generation in animals deficient in FVIII or FIX with and without inhibitors ( 29 ). In the ex vivo experiments, spiking haemophilia plasmas with MG1113 increased thrombin generation in a concentration-dependent fashion.…”
Section: Mg1113mentioning
confidence: 99%